An Investigation of School leadership in the Effective Implementation of Bilingual Education in Indonesia: A Case Study - H. S., David Yong; Marpaung, Agus Salim; Sibarani, Berlin; Murni, Sri Minda (International Journal of Humanities and Education Development (IJHED), 2024)
This study explores how school leadership impacts the successful implementation of bilingual education in Indonesia, focusing on three schools. Bilingualism offers many benefits, including better cognitive skills, cultural understanding, and economic opportunities. Effective school leadership is crucial in creating supportive policies, providing resources, and fostering environments where bilingual education can thrive. Through interviews with three principals and two heads of departments, the study examines their leadership practices, challenges, and strategies. The analysis identified key themes: inclusive and resilient leadership, proactive community collaboration, overcoming challenges like limited resources and teacher shortages, and maintaining a clear vision for bilingual education. The findings show that good leadership involves ongoing professional development, inclusive decision-making, and smart resource management. These practices help tackle obstacles and improve bilingual education programs. The study highlights the importance of visionary leadership in promoting language diversity, educational fairness, and social harmony in implementing bilingual education in Indonesia..